Selective sweep sites and SNP dense regions differentiate Mycobacterium bovis isolates across scales - Legall, Noah; Salvador, Liliana C. M. (Frontiers in Microbiology, 2022)
Mycobacterium bovis, a bacterial zoonotic pathogen responsible for the economically and agriculturally important livestock disease bovine tuberculosis (bTB), has shown characteristics of a generalist pathogen, infecting worldwide a broad range of mammalian species. These characteristics have led to bidirectional transmission events between livestock and wildlife species and to the formation of wildlife reservoirs, impacting the ability of bTB control measures. Next Generation Sequencing (NGS) has transformed our ability to understand disease transmission events by tracking variant sites. However, genomic factors related to host adaptation following spillover, alongside the role of other genomic processes in the M. bovis transmission process are understudied problems. In this study, we analyzed publicly available M. bovis datasets collected from multiple hosts from three countries with bTB endemic regions (United Kingdom, United States of America, and New Zealand) to investigate if specific M. bovis genomic signatures (namely homologous recombination and/or sites of positive selection) are related to M. bovis evolution at the host-species, geographical, and/or sub-population levels. Regions predicted to be impacted by homologous recombination were found to affect multiple genes (impacting processes such as lipid metabolism, cell wall architecture, and virulence). Amongst these genes, homologous recombination in Mb3510c, Mb0403, and rpfA were considered important in distinguishing between the different organizational scales. New Zealand isolates were also found to have highly significant selective sweep sites amongst a certain population cluster, suggesting a limited role for selective sweeps in conferring adaptive changes to M. bovis. The results of this study highlight the usefulness of comparing multiple host-associated isolates to understand genomic signatures that lead to a better understanding of host-pathogen interactions.